ORBITAL IMAGES FOR SPATIAL AND TEMPORAL CHARACTERIZATION OF VINEYARD BY VEGETATION INDEX IN THE "CAMPANHA GAÃšCHA" WINE REGION, BRAZIL - Pauletto, Henrique; Hoff, Rosemary; Junges, Amanda Heemann; Valenti, Eduardo da Silva; Alberti, Rodrigo (REVISTA DE AGRICULTURA, 2022)
Remote sensing has become an important technique for spatial characterization and agricultural monitoring, in order to improve wine development and reduce production costs. The wine region of the â€œCampanha GaÃºchaâ€, Brazil, was recognized in 2020 as an Indication of Origin for quality wines. This study analyzed orbital data in a â€œCabernet sauvignonâ€ vineyard in the municipality of Santana do Livramento. From the images of the Planet and Sentinel-2 satellites, the Normalized Difference Vegetation Index (NDVI) was evaluated, as well as its viability in viticulture in the region. Twelve images from each satellite were analyzed using digital image processing techniques, average NDVI temporal profiles were generated and analyzed by statistical methods. The generated maps produced zoning for each scene over the period studied, for both satellite images. The results showed that the two satellites were suitable for use in monitoring vineyards, due to their excellent temporal, spatial and radiometric resolution.